Case reportBilateral episcleral brachytherapy in simultaneous choroidal melanoma and circumscribed hemangioma - Correa-Pérez, María Encarnación; Saornil, María Antonia; García-Álvarez, Ciro; Lopez-Lara Martín, Francisco; Frutos-Baraja, Jesus María (Journal of Contemporary Brachytherapy, 2013)
Purpose: To describe the efficacy of episcleral brachytherapy in a choroidal melanoma and circumscribed hemangioma arising in both eyes of the same patient. Case report : We present the case of a 47 year old man who presented decreased visual acuity a few months preceding initial consult. On fundoscopy, he presented a melanotic lesion in the right eye, and a red-orange choroidal mass in the macular area of the left eye. Material and methods: B scan-ultrasound, fluorescein, and indocyanine green angiography, confirmed the diagnosis of choroidal melanoma in the right eye, and circumscribed choroidal hemangioma in the left eye. Episcleral brachytherapy with 125 I was performed in both eyes consecutively. Results and Conclusions : Bilateral episcleral brachytherapy successfully treated both tumors, preserving the eyes and useful visual function.